COMMON PROBLEMS FACED BY FOREIGN LANGUAGE LEARNERS - Xoliqova Xumora Jahongir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Learning a foreign language as a second language presents unique challenges, particularly when the learning environment doesn't offer constant exposure to the target language. This lack of immersion can hinder progress, even for motivated learners. These difficulties can be viewed as obstacles, requiring effective strategies to overcome. This article identifies common problems faced by second language learners and explores possible solutions, drawing upon scholarly insights to address the causes of these issues.